International Librarianship Developing Professional, Intercultural, and Educational Leadership - Miller, Michael J. (State University of New York Press, 2016)
International librarianship stems from a desire to bring about political change, transcultural understanding, collaboration, and mutual respect. Historically, librarians have been deeply involved with challenging issues of information sharing, equity in information access, and bridging the digital divide between different socioeconomic communities. This collection draws on case studies from American librarians who traveled to Central America, the Caribbean, Central Europe, Africa, the Mediterranean, and Asia to participate in librarian-initiated and sponsored projects. They united communities, promoted religious and cultural tolerance, developed new facilities, or enhanced existing libraries and archives, thereby enriching communities with resources, professional expertise, new partnerships, and sustainable development practices. International Librarianship offers insight into how these experiences might serve as templates and promote best practices in collaborations within the library profession in the United States and abroad, and it also demonstrates how international experiences can enliven home institutions upon return.